2019
DOI: 10.5194/tc-2019-76
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pingo development in Grøndalen, West Spitsbergen

Abstract: Pingos are common features in permafrost regions that form by subsurface massive-ice aggradation and create hill-like landforms. Pingos on Spitsbergen have been previously studied to explore their structure, formation timing, connection to springs as well as their role in post-glacial landform evolution. However, detailed hydrochemical and stable-15 isotope studies of massive ice samples recovered by drilling has yet to be used to study the origin and freezing conditions in pingos. Our core record of 20.7 m th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In the coring of marine‐based pingos in Grøndalen, Demidov et al. (2019) demonstrate massive ice exceeding 20 m in thickness beneath a pingo of 9 m height. Whilst numerical simulations of palsas and lithalsas analogous to our proposed structure of Lagoon Pingo have demonstrated that segregation ice can produce ∼6 m of heave over a period of 150 years (An & Allard, 1995), further coring is necessary to validate the precise architecture of frozen ground within these pingos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the coring of marine‐based pingos in Grøndalen, Demidov et al. (2019) demonstrate massive ice exceeding 20 m in thickness beneath a pingo of 9 m height. Whilst numerical simulations of palsas and lithalsas analogous to our proposed structure of Lagoon Pingo have demonstrated that segregation ice can produce ∼6 m of heave over a period of 150 years (An & Allard, 1995), further coring is necessary to validate the precise architecture of frozen ground within these pingos.…”
Section: Discussionmentioning
confidence: 99%
“…Liestøl, 1977) and, (c) those occurring in nearshore or low‐lying environments, undergoing glacio‐isostatic uplift. Despite this categorization of their hydraulic properties, the mechanism and processes which govern pingo formation still remain poorly understood (Demidov et al., 2019; Gurney, 1998; Kunz & Kneisel, 2021), and studies assessing early pingo forms remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…The fine-grained Holocene muds and clays are frost-susceptible, and arguably more conducive to the formation of segregation ice (Smith, 1985). This dependence of sedimentary context is perhaps best highlighted in cores of pingos below the Holocene marine limit in Grøndalen, Svalbard (Demidov et al, 2019). Within these, massive ice is confined exclusively within assemblages of non-marine gravelly sands and loams.…”
Section: Pingos and Segregation Icementioning
confidence: 99%
“…Yet despite a recent appreciation for their role as a conduit of methane through continuous permafrost, open-system pingos are poorly understood (e.g. Gurney, 1998;Demidov et al, 2019;Kunz and Kneisel, 2021). Firstly, uncertainty remains regarding their structural composition.…”
Section: Research Context and Motivationmentioning
confidence: 99%
See 1 more Smart Citation